Advancing alcohol research and treatment: Contentions and debates about treatment intensity, goals and outcomes in the 1970s and 1980s - Allsop, Steve (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 Society for the Study of Addiction. Aims: This narrative exploration of alcohol treatment research focuses on key contentions and advances in alcohol treatment during the critical 1970s and 1980s. Methods: Papers and books which signal some of the major debates and advances in alcohol treatment research were selected from the 1970s and 1980s. The selection process was based on significant debate during this period, and included those that influenced the field in general and this author in particular. Results: This was a period where challenges to traditional models and concepts, and the perceived universal need for long-term treatment, were accompanied by contention but also advances in research and treatment approaches. The debates and advances resonate today. These include the recognition that: intensive and long-term treatment is not always required; for dependent drinkers, relapse is a common treatment outcome meriting specific treatment approaches to prevent and reduce this risk; controlled drinking is a treatment option, especially for younger and less dependent drinkers; and an important contributor to enduring change is access to, and realization of, improvements in the quality of life. Conclusions: Pioneering research and publications in the 1970s and 1980s, sometimes conducted and produced in contentious contexts, influenced significantly conceptualizations of alcohol-related problems, and laid the foundations for treatment hypotheses and research, improving access to a broader range of evidence-based treatment. These underpinning works influenced the development of stepped-up care from brief to intensive interventions, relapse prevention and treatment options not limited to abstinence, and they identified the need to include a stronger focus on quality of life.